2023
DOI: 10.3389/fimmu.2023.1130214
|View full text |Cite
|
Sign up to set email alerts
|

Utility of monocyte HLA-DR and rationale for therapeutic GM-CSF in sepsis immunoparalysis

Abstract: Sepsis, a heterogeneous clinical syndrome, features a systemic inflammatory response to tissue injury or infection, followed by a state of reduced immune responsiveness. Measurable alterations occur in both the innate and adaptive immune systems. Immunoparalysis, an immunosuppressed state, associates with worsened outcomes, including multiple organ dysfunction syndrome, secondary infections, and increased mortality. Multiple immune markers to identify sepsis immunoparalysis have been proposed, and some might o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 151 publications
1
13
0
1
Order By: Relevance
“…This study revealed that mHLA‐DR was an independent risk factor (OR = 0.939; 95% CI: 0.892–0.988; p = 0.016) for poor outcomes in EHS patients. We found that mHLA‐DR levels had a modest prognostic effect for in‐hospital mortality rate (AUC = 0.880, 95% CI: 0.780–0.945, cut‐off value = 53.6%, p < 0.0001) in EHS, which was consistent with the previous studies illustrating that decreased mHLA‐DR expression predicted poor outcomes in patients with severe burns, 20 and sepsis 15 . Berres et al have described that individuals with decompensated liver cirrhosis had greater ICU mortality rate when their mHLA‐DR levels were decreased 10 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study revealed that mHLA‐DR was an independent risk factor (OR = 0.939; 95% CI: 0.892–0.988; p = 0.016) for poor outcomes in EHS patients. We found that mHLA‐DR levels had a modest prognostic effect for in‐hospital mortality rate (AUC = 0.880, 95% CI: 0.780–0.945, cut‐off value = 53.6%, p < 0.0001) in EHS, which was consistent with the previous studies illustrating that decreased mHLA‐DR expression predicted poor outcomes in patients with severe burns, 20 and sepsis 15 . Berres et al have described that individuals with decompensated liver cirrhosis had greater ICU mortality rate when their mHLA‐DR levels were decreased 10 .…”
Section: Discussionsupporting
confidence: 91%
“…Besides, platelet (PLT), hemoglobin (Hb), and hematocrit (HCT) levels were lower in nonsurvivors (p < 0.05), indicating possible massive destruction of red blood cells in nonsurvivors. Furthermore, the length of ICU stays and hospital stays in those nonsurvivors (16 [9-20] days and 18 [9-46] days) were both longer than those in survivors (5 [3][4][5][6][7][8] days, p < 0.001 and 11 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] days, p = 0.045). Mean arterial pressure, white blood cell, neutrophil count and percentage, prolonged activated partial thromboplastin time, fibrinogen, serum creatinine, creatine kinase, lymphocyte count and percentage, SIRS and International Society of Thrombosis and Hemostasis score, underlying disease, monocyte count and percentage, and RM between survivors and nonsurvivors were not significantly different.…”
Section: Baseline Characteristics Of Ehs Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Einerseits konnte eine therapeutische Stimulation der mHLA-DR-Expression mittels Substitution von Interferonγ bereits positive Effekte erzielen [54], was aktuell in weiteren Studien erneut evaluiert wird [55]. Andererseits zeigten sich auch positive Effekte einer GM-CSF-Gabe als myelopoetischem Wachstumsfaktor mit konsekutiver immunaktivierender Wirkung bei primärer Immunparalyse [56,57,58]. Im Fokus der immunaktivierenden Therapiekonzepte steht hierbei die Restitution des Immunsystems.…”
Section: Merkeunclassified